STUDENTS TEACHING SKILL ON MICROTEACHING AT PHYSICS EDUCATION DEPARTEMENT - Ino Angga Putra; Novia Ayu Sekar Pertiwi; Kartika Wulandari (Jurnal Pendidikan Fisika, 2020)
This study aims to determine the basic skills of teaching prospective teacher students in microteaching courses. This type of research is a qualitative descriptive study. The research design is survey research. The research population used was students of the Physics Education Study Program UNWAHA. The assessment instrument in the study is the instrument / rubric for assessing the basic skills of teaching prospective teacher students. Research data collection by observing the implementation of student learning by observers of 3 lecturers with 3 observations. The assessment instrument uses a Likert scale with a scale of 1-4. The research data obtained were in the form of an average rating of basic teaching skills (quantitative data) and the results of comments from observers (qualitative data). The results showed that prospective teacher students in the category were good enough on the average assessment of basic teaching skills with a value of 2.80. It is expected that prospective teacher students improve their questioning skills, variety skills, guiding discussion skills and class management skills in Microteaching activities